Concepts of Biology - Fowler, Samantha; Roush, Rebecca; Wise, James (Open textbook library., 2013)
Concepts of Biology is designed for the introductory biology course for nonmajors taught at most two- and four-year colleges. The scope, sequence, and level of the program are designed to match typical course syllabi in the market. Concepts of Biology includes interesting applications, features a rich art program, and conveys the major themes of biology. OpenStax College has compiled many resources for faculty and students, from faculty-only content to interactive homework and study guides.